A biomechanical evaluation of resistance: Fundamental concepts for training and sports performance - Frost, D. M.; Cronin, J.; Newton, R. U. (Sports Medicine, 2010)
Newton's second law of motion describes the acceleration of an object as being directly proportional to the magnitude of the net force, in the same direction as the net force and inversely proportional to its mass (a=F/m). With respect to linear motion, mass is also a numerical representation of an object's inertia, or its resistance to change in its state of motion and directly proportional to the magnitude of an object's momentum at any given velocity. To change an object's momentum, thereby increasing or decreasing its velocity, a proportional impulse must be generated. All motion is governed by these relationships, independent of the exercise being performed or the movement type being used; however, the degree to which this governance affects the associated kinematics, kinetics and muscle activity is dependent on the resistance type. Researchers have suggested that to facilitate the greatest improvements to athletic performance, the resistance-training programme employed by an athlete must be adapted to meet the specific demands of their sport. Therefore, it is conceivable that one mechanical stimulus, or resistance type, may not be appropriate for all applications. Although an excellent means of increasing maximal strength and the rate of force development, free-weight or mass-based training may not be the most conducive means to elicit velocity-specific adaptations. Attempts have been made to combat the inherent flaws of free weights, via accommodating and variable resistance-training devices; however, such approaches are not without problems that are specific to their mechanics. More recently, pneumatic-resistance devices (variable) have been introduced as a mechanical stimulus whereby the body mass of the athlete represents the only inertia that must be overcome to initiate movement, thus potentially affording the opportunity to develop velocity-specific power. However, there is no empirical evidence to support such a contention. Future research should place further emphasis on understanding the mechanical advantages/disadvantages inherent to the resistance types being used during training, so as to elicit the greatest improvements in athletic performance.